INDIVIDUAL FUTURE ORIENTATION AND DEMOGRAPHIC FACTORS PREDICTING LIFE SATISFACTION - Koļesovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This study explored a model of prediction of life satisfaction by individual future orientation (FO) and demographic factors. Individual views of the future and goals are closely associated with well-being. Theories of FO represent different approaches to its conceptualization. Following Seginer (2009), this study presents a combination of motivational, cognitive, and behavioral components of FO. Participants were 130 females and 75 males from 18 to 49. A new measure of individual FO (the Individual Future Orientation Scale, IFOS) and the Satisfaction With Life Scale (Diener, Emmons, Larsen, & Griffin, 1985) were used for the assessment. The results of structural equation modeling demonstrate that relatively higher life satisfaction is predicted by higher individual FO and higher income assessed as an income range and subjective satisfaction with it. Therefore, subjective involvement in a pursuit of future goals and financial background add to understanding of individual satisfaction with life.